Radical nationalism in India, 1930-42 : the role of the All India Congress Socialist Party - Masani, Z (1976)
The central problem to which this thesis addresses itself is the attempt of the All India Congress Socialist Party (CSP) to establish itself as a radical nationalist alternative to both the Gandhian leadership of the Indian National Congress and the Communist Party of India (CPI). The problem has two main dimensions: one, the role of the CSP as a left-wing of the Congress, in relation to its leadership and rank and file; the other, the CSP's role as an autonomous party outside the Congress, in its relations with the Communists and other radical groups in non-Congress mass organisations. Continued in thesis ...